Psychosocial interventions after tsunami in Tamil Nadu, India - Lakshmi Vijaykumar ; R. Thara ; Sujit John ; Shanti Chellappa (International Review of Psychiatry, June 2006; 18(3): 225-231, 2006)
Any response to the mental health needs of the affected community following any disaster depends upon a number of factors, including disaster preparedness, existence of mental health services, resources in human and financial terms, along with the magnitude, cause and suddenness of the event. In India, groups of islands in the Bay of Bengal and the coast of Tamil Nadu were very badly hit. The survivors needed basic physical and emotional support. The response by two non-governmental organizations (NGOs) is described in this paper. Normalization was seen as an important first step. Using a number of training materials, volunteers were trained to deal with the mental health needs of the survivors. A consistent well resourced and accessible mental health network is necessary for appropriate intervention.